The role of learning outcomes in national qualification frameworks - Raffe, David [Verfasser] (My University, 2011)
"This chapter explores the spread of National Qualfications Frameworks (NQFs) and examines the role of learning outcomes within them. It describes two contrasting types of NQFs - outcomes-led and outcomes-referenced - and suggests that these are associated with different roles for learning outcomes. It reviews evidence which suggests that outcomes referenced frameworks, in which learning outcomes play a less central role, have been more effective. It argues that are need to move beyond the polarised debates about learning outcomes to define a positive but modest role for outcomes within qualifications systems and NQFs." (Autorenreferat, BIBB-Doku)
Keywords: S 2.2.4 Anrechnung, Prüfung & Zertifizierung; Anrechnung von Bildungsleistungen; Lernergebnisorientierung; Nationaler Qualifikationsrahmen